Hypoxia-Reoxygenation Induced Cardiac Mitochondrial Dysfunction - Gül Şimşek; Hilmi Burak Kandilci (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:Cellular response to low oxygen tension is altered by severity and duration of hypoxia. Although the subject has been studied extensively, mechanisms leading to hypoxia-reoxygenation damage remain undefined. Here, we investigated the effect of long term continuous hypoxia (48 hours) on cardiac derived HL-1 cells, mainly the role of mitochondria in cellular energy and reactive oxygen species homeostasis.Materials and Methods:In this study, mammalian atrium derived HL-1 cells were cultured either in long term hypoxia (48 hours, 1% O2) or in normoxia (48 hours, 21% O2) conditions. Mitochondrial membrane potential and reactive oxygen species (ROS) level was measured using florescent dyes in a confocal microscope. GAPDH protein levels were detected by western blotting in normoxic control and hypoxic cells.Results:Present results demonstrate that, 48 hours of hypoxia did not alter baseline mitochondrial membrane potential and its oxidative respiration capacity in cardiac HL-1 cells. The mitochondrial depolarization response to in reoxygenation period of oxygen deprived cells was slower in hypoxic cells. In hypoxic cells, basal ROS levels were higher whereas hydrogen peroxide response was smaller when compared with the normoxic control group. GAPDH protein levels were unaltered between groups.Conclusion:Present results indicate that, persistent mitochondrial oxidation phosphorylation uncoupling may lead to an over production of ROS.